2011
DOI: 10.2166/wst.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Influent concentrations and removal performances of metals through municipal wastewater treatment processes

Abstract: This extensive study aimed at quantifying the concentrations and removal efficiency of 23 metals and metalloids in domestic wastewater passing through full-scale plants. Nine facilities were equipped with secondary biological treatment and three facilities were equipped with a tertiary treatment stage. The metals investigated were Li, B, Al, Ti, V, Cr, Fe, Ni, Co, Cu, Zn, As, Se, Rb, Mo, Ag, Cd, Sn, Sb, Ba, TI, Pb and U. Particulate and dissolved metals were measured using 24 h composite samples at each treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Chipasa (2003) concluded that metals removals were directly proportional to metal influent concentrations, with low removals of Cd and Pb when their influent concentrations were about 20 and 50 lg/l, respectively. This conclusion does not seem to be in agreement with the results obtained by other that present significant removals for Cd with influent concentrations near or below that value (Choubert et al 2011a;Buzier et al 2006;Karvelas et al 2003;Goldstone et al 1990a). However, the biological process is quite different in the Gdansk WWTP, with an ASP configured to enhance biological nutrient removal, which may influence the mechanisms associated with the metals removal.…”
Section: Ascontrasting
confidence: 80%
See 2 more Smart Citations
“…Chipasa (2003) concluded that metals removals were directly proportional to metal influent concentrations, with low removals of Cd and Pb when their influent concentrations were about 20 and 50 lg/l, respectively. This conclusion does not seem to be in agreement with the results obtained by other that present significant removals for Cd with influent concentrations near or below that value (Choubert et al 2011a;Buzier et al 2006;Karvelas et al 2003;Goldstone et al 1990a). However, the biological process is quite different in the Gdansk WWTP, with an ASP configured to enhance biological nutrient removal, which may influence the mechanisms associated with the metals removal.…”
Section: Ascontrasting
confidence: 80%
“…Cr, Ni, Zn) even between plants without relevant industrial contribution. Choubert et al (2011a) within an extensive study dealing with the fate of xenobiotics through full-scale WWTPs in France (AMPERES project), in samples collected from nine WWTPs (described in Table 3), found that metal contents in the influent were highly variable between the WWTPs and also within each WWTP. The comparison between rural and urban wastewaters confirmed that urban areas with higher industrial contribution released more metals.…”
Section: Asmentioning
confidence: 99%
See 1 more Smart Citation
“…> 0.45 μm). At WWTWs, Cu and Pb are known to have a high affinity for the particulate fraction (Karvelas et al 2003;Buzier et al 2006) and, thus, can be removed by physical separation (Choubert et al 2011). Conversely, Ni and Zn abound in the soluble fraction, which requires adsorption/ion exchange processes or chemical modification for their effective elimination (Martin et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while RO removal was consistently better than 90% except for boron (Van Buynder et al 2009), frequent detections at low concentrations were still recorded in RO permeate. Metals are sourced from both urban and industrial catchments, and frequent detections in secondary WW are often related to incomplete removal during WW treatment as well as very high concentrations in influent wastewater (Busetti et al 2005;Choubert et al 2011). Complexing agents are also used broadly, poorly removed by conventional WWTPs (Oviedo and Rodriguez 2003), and commonly detected in μg/L-concentrations in secondary WW (Reemtsma et al 2006).…”
Section: Occurrence Of Chemicals In Ro Permeatementioning
confidence: 99%